The political economy of relief aid allocation: Evidence from Madagascar - Francken, Nathalie; Minten, Bart; Swinnen, Johan (Elsevier, 2012)
This paper studies the political economy of relief allocation using evidence from aid programs after cyclone Gafilo hit Madagascar in 2004. Relief was provided by the government as well as local and international aid agencies. Aid was more likely in areas with a higher need for relief, in more easily accessible communes and in cyclone-affected communes with higher radio coverage and stronger political support for the government. Compared to relief provided by the government, aid by agencies was less affected by media or political factors, but more likely to go to poorer and more easily accessible communes, unconditional on impact.